2010
DOI: 10.1017/s0265051709990210
|View full text |Cite
|
Sign up to set email alerts
|

Informal music learning, improvisation and teacher education

Abstract: I n t r o d u c t i o n : I n f o r m a l l e a r n i n g a n d t h e d e v e l o p m e n t o f a c r i t i c a l p e r s p e c t i v e t o w a r d s m u s i c e d u c a t i o nAt the age of four, a child I knew drew extraordinarily vibrant, imaginative trees. Crayon, chalk, colored pen, and silly putty were all useful. These trees were remarkable in how clearly they showed the bulbous lobes and branchy veins of individual leaves in a kind of cubist, all-the-way-around view that would have delighted Picasso. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
93
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 25 publications
1
93
0
2
Order By: Relevance
“…While her study was limited to choral music education candidates and jazz improvisation, further research may help to suggest instructional treatments that would help all undergraduate music education majors increase confidence in teaching multiple forms of improvisation. Wright and Kanellopoulos (2010), for example, described the effects of a course in free improvisation on perceptions of 91 student teachers from two Greek universities. Using narrative methodology to study participant journals and reflections, the researchers found that improvisation helped to foster positive student teacher dispositions toward embracing informal pedagogies in music education, and to develop more critical analyses of theory and practice.…”
Section: Discussionmentioning
confidence: 99%
“…While her study was limited to choral music education candidates and jazz improvisation, further research may help to suggest instructional treatments that would help all undergraduate music education majors increase confidence in teaching multiple forms of improvisation. Wright and Kanellopoulos (2010), for example, described the effects of a course in free improvisation on perceptions of 91 student teachers from two Greek universities. Using narrative methodology to study participant journals and reflections, the researchers found that improvisation helped to foster positive student teacher dispositions toward embracing informal pedagogies in music education, and to develop more critical analyses of theory and practice.…”
Section: Discussionmentioning
confidence: 99%
“…Informal music pedagogy, then, intentionally embeds both music making and characteristics of informal learning into a learning environment. Such characteristics include social aspects of relationship, non-linear and holistic play, interactive and self-directed processes, and immersion into and exploration of music making possibilities (Campbell, 2001;Harwood & Marsh, 2012;McPhail, 2013;Wright & Kanellopoulos, 2010). These same characteristics have been observed as aspects of young children's ways of being musical; the purpose of music is for relationship (Bartel & Cameron, 2007), musical behaviors are holistically woven into play (Campbell, 2010;Lamont, 2008;Young, 2003), ownership roles are taken by the child in directing self and others (Elkind, 2007;Sommer, Samuelsson, & Hundeide, 2010), and immersion in a musical environment with opportunity to explore and respond is important for processes of musical development (Gordon, 2013;Reynolds, 2006).…”
Section: Situating the Studymentioning
confidence: 99%
“…The successful completion of the activity yielded improvements in their perception of their own musical ability, as well as their ability to teach music in the classroom. Wright and Kanellopoulos (2010) conducted narrative research in two Greek universities in which they provided teacher candidates with a course in Improvisation in Music Education. Participants reported the experience to be free of the fear and intimidation, so often at the core of traditional music instruction.…”
Section: Fear Of Teaching Musicmentioning
confidence: 99%